2015
DOI: 10.1007/s12262-015-1292-x
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in the Surgical Treatment of Retroperitoneal Sarcomas

Abstract: The objective of this study is to assess long-term prognosis and patterns of failure in patients with retroperitoneal sarcoma who underwent surgery with curative intent at a single institution. We also provide a thorough review of the literature including several series and widely variable data regarding local and distant failure. During a 25-year period , 45 consecutive patients who underwent surgery for retroperitoneal sarcoma at a single referral center were reviewed retrospectively. We recorded and analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 20 publications
1
11
0
7
Order By: Relevance
“…The adverse effect of incomplete resection (R2) on OS was also reported (HR=3.50; 95% CI=1.15-10.65; p=0.027). With regards to recurrence rates, those reported in the literature range between 26% and 49% depending on the follow-up period (16,25,31,34). The recurrence rate in our study over a follow-up period of 83 months was 43.33%, which is in fact almost identical to the rates reported for other cohorts with similar or longer followup when using the same surgical approach (contiguously involved organ resection) (25,29,31,34).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The adverse effect of incomplete resection (R2) on OS was also reported (HR=3.50; 95% CI=1.15-10.65; p=0.027). With regards to recurrence rates, those reported in the literature range between 26% and 49% depending on the follow-up period (16,25,31,34). The recurrence rate in our study over a follow-up period of 83 months was 43.33%, which is in fact almost identical to the rates reported for other cohorts with similar or longer followup when using the same surgical approach (contiguously involved organ resection) (25,29,31,34).…”
Section: Discussionsupporting
confidence: 85%
“…The demographics of our study population are similar to those of other published series. Liposarcoma is the most common histology (59%) followed by leiomyosarcoma (17%) (3,4,31), the majority of patients present with a tumor size between 10 and 33 cm and over half of all patients present with medium-/ high-grade tumors (57%) (3,13,14,17,24,25,32,33). The prognostic significance of high tumor grade as predictor of recurrence (p=0.014) and tumor related death (p=0.031) was recorded, again in line with larger published series (4,10,23,25,32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The surgical resection of RPLM can be associated with significant morbidity given that they usually invade important vascular structures such as the inferior vena cava (IVC) and tributaries, the duodenum and the ureter (11). The intraoperative 30-day mortality rate has been reported to be as high as 15% in resections of RPLMs arising from the IVC (12). However, a curative intent operation entails a wide resection incorporating the tumor and all the involved structures (e.g duodenum, colon, kidney, IVC) in order to achieve adequate resection margins (13).…”
Section: Discussionmentioning
confidence: 99%
“…A multivariate analysis [ 22 ] of the predictive risk factors for AL after small bowel and colorectal anastomoses found that although drains were used in more than 90% of patients, the use of drains did not confer a significant benefit to the patients as 12.4% of drained patients developed AL compared to 15% of nondrained patients (OR = 1.06, p = 0.92). Summary of the studies that concluded no clinical benefit of routine drainage after colorectal anastomosis is illustrated in Table 2 .…”
Section: Antidrainagementioning
confidence: 99%